Hubungan Pengetahuan Dan Dukungan Keluarga Dengan Keberhasilan Pemberian Asi Ekslusif Pada Ibu Menyusui Di Wilayah Kerja Puskesmas Ulak Tanding Rejang Lebong - Umami, Desi Aulia; Iswari, Indra; Sari, Eka Agustina (Universitas Dehasen Bengkulu, 2025)
Good family support for the mother will help the success of exclusive breastfeeding. Family support will make the mother feel calm, thereby facilitating breast milk production. The aim of this research is to determine the relationship between knowledge and family support and exclusive breastfeeding at the Ulak Tanding Community Health Center, Rejang Lebong Regency, Bengkulu Province. The design used in analytical survey research is a cross sectional design. The population in this study were women of childbearing age at the Ulak Tanding Community Health Center, Rejang Lebong Regency for the period January-May 2024, totaling 514 people. The sample in this study was 84 respondents. Sampling was taken by purposive sampling. The research results were obtained from 84 respondents, almost half of the respondents (44%) had insufficient knowledge. Of the 84 respondents, the majority of respondents (53.6%) had families supporting exclusive breastfeeding. Of the 84 respondents, most of the respondents (53.6%) families supported exclusive breastfeeding and almost half of the respondents (46.4%) families did not support exclusive breastfeeding. There is a relationship between knowledge and exclusive breastfeeding at the Ulak Tanding Community Health Center, Rejang Lebong Regency, Bengkulu Province. There is a relationship between family support and exclusive breastfeeding at the Ulak Tanding Community Health Center, Rejang Lebong Regency, Bengkulu Province.